NEW FUNCTIONALIZED GLASS FIBERS EMPLOYING CALIXARENIC SYSTEMS - SEPTELEAN, Raluca; VELNAZAROV, Myrat; PRODAN, Doina; PERHAIȚĂ, Ioana; NEMEȘ, Ovidiu; MOLDOVAN, Marioara (Studia Universitatis Babeș-Bolyai Chemia, 2017)
New precursors for functionalized grass fibres were obtained through deposition of functionalized calix[4]arenes on G14 short glass fibers. The methods employed for the preparation as well as the characterization by thermal analysis, FT-IR spectroscopy, TEM and SEM microscopy of the newly obtained materials is presented.